1982
DOI: 10.1113/jphysiol.1982.sp014087
|View full text |Cite
|
Sign up to set email alerts
|

Branching of muscle spindle afferents of jaw closing muscles in the cat.

Abstract: SUMMARY1. Functionally isolated single fibres were prepared from the cut central ends of the masseter nerve in cats. Of those firing in response to muscle stretch, most were alpha motor units but some had the properties of afferent fibres innervating muscle receptors.2. These afferent units were remarkably sensitive to muscle stretch even under anaesthesia deep enough to eliminate all stretch evoked e.m.g. activity in masseter. Moreover, these units responded to gentle pressing of the surface of either the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Of the other units, one was thought to be a masseter spindle afferent, and four temporalis spindle afferents. Similar units have been reported in masseter nerve filaments by Kato, Kawamura & Morimoto (1982), who suggested that their presence in the central ends of cut masseter nerve filaments could be explained on the basis of branching by a parent axon to innervate more than one muscle spindle. If this explanation is correct, the above results would suggest that an axon can branch to innervate spindles in different closely related muscles (i.e.…”
Section: Resultssupporting
confidence: 81%
“…Of the other units, one was thought to be a masseter spindle afferent, and four temporalis spindle afferents. Similar units have been reported in masseter nerve filaments by Kato, Kawamura & Morimoto (1982), who suggested that their presence in the central ends of cut masseter nerve filaments could be explained on the basis of branching by a parent axon to innervate more than one muscle spindle. If this explanation is correct, the above results would suggest that an axon can branch to innervate spindles in different closely related muscles (i.e.…”
Section: Resultssupporting
confidence: 81%
“…Not only did noradrenergic drive intensify the magnitude of the masseteric reflex, it also induced a potent increase in reflex duration. During baseline conditions, reflex activation increased masseter tone for 11 s even though reflex pathways were continuously activated for 20 s. This response occurs because Ia spindle afferents rapidly adapt to persistent activation by slowing their discharge activity; this reduces muscle tone by reducing glutamate release on to motoneurones (Kato et al 1982; Chandler, 1989). However, when noradrenergic drive on to motoneurones was increased, masseter tone was elevated throughout the entire reflex activation period.…”
Section: Discussionmentioning
confidence: 99%
“…6). The short‐lived nature of this response presumably results from the initial activation of Ia spindle afferents, which then rapidly adapt to continued muscle stretch (Hulliger, 1979; Kato et al 1982).…”
mentioning
confidence: 99%